2021
DOI: 10.3390/molecules26133807
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins: Promising Natural Products with Diverse Pharmacological Activities

Abstract: Anthocyanins are natural products that give color to plants. As natural plant pigments, anthocyanins also have a series of health-promoting benefits. Many researchers have proved that anthocyanins have therapeutic effects on diseases, such as circulatory, nervous, endocrine, digestive, sensory, urinary and immune systems. Additionally, a large number of studies have reported that anthocyanins have an anticancer effect through a wide range of anti-inflammatory and antioxidant effects. The anti-disease impact an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 134 publications
1
62
0
3
Order By: Relevance
“…ACNs are well documented for their antioxidant, antiinflammatory, and anti-apoptotic effects on human health (Henriques et al, 2020;Kozłowska and Dzierżanowski, 2021;Liu et al, 2021;Pérez-Torres et al, 2021;Vega-Galvez et al, 2021). ACNs could be rapidly absorbed in the stomach and detected in the blood and urine (Fang, 2014;Tian et al, 2019), so these pigments are recognized as one of the leading nutraceuticals for prolonging health benefits through the attenuation of chronic, non-communicable diseases, including cancers, obesity, diabetes, cardiovascular diseases, and neurodegenerative diseases.…”
Section: Anthocyanins and Their Biological Effects On Chronic Diseasesmentioning
confidence: 99%
“…ACNs are well documented for their antioxidant, antiinflammatory, and anti-apoptotic effects on human health (Henriques et al, 2020;Kozłowska and Dzierżanowski, 2021;Liu et al, 2021;Pérez-Torres et al, 2021;Vega-Galvez et al, 2021). ACNs could be rapidly absorbed in the stomach and detected in the blood and urine (Fang, 2014;Tian et al, 2019), so these pigments are recognized as one of the leading nutraceuticals for prolonging health benefits through the attenuation of chronic, non-communicable diseases, including cancers, obesity, diabetes, cardiovascular diseases, and neurodegenerative diseases.…”
Section: Anthocyanins and Their Biological Effects On Chronic Diseasesmentioning
confidence: 99%
“…Several studies have suggested that treatment with protective compounds that inhibit oxidative stress and inflammation could reduce the amount of photoreceptor cell death in animal models of light-induced retinal damage (LD) [ 8 , 9 , 10 ]. In particular, exogenous compounds belonging to carotenoid or anthocyanin families, such as lutein and cyanidin-3-glucoside (C3G), have been recognized among the most promising substances capable to prevent/counteract oxidative stress through a direct free radical scavenging effect [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional efficacy of C3G depends on its capability to stimulate rhodopsin regeneration in the outer retina [ 20 ]. In response to oxidative stress, the antioxidant and anti-inflammatory properties of lutein or C3G result in improved retinal function presumably through reduced photoreceptor death [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, anthocyanins, cyanidin, and their derivatives possess cardioprotective activity due to their antioxidant, anti-inflammatory actions, and inhibiting endothelial dysfunction and NO production. 56 Chlorogenic acid and quercetin- O -glucoside also had a cardioprotective, 57,58 and anti-depressant actions. 59,60 …”
Section: Resultsmentioning
confidence: 99%